Genotypic variation in foundation species generates network structure that may drive community dynamics and evolution. Issue 3 (March 2016) - Lau, Matthew K.; Keith, Arthur R.; Borrett, Stuart R.; Shuster, Stephen M.; Whitham, Thomas G.
Abstract: Although genetics in a single species is known to impact whole communities, little is known about how genetic variation influences species interaction networks in complex ecosystems. Here, we examine the interactions in a community of arthropod species on replicated genotypes (clones) of a foundation tree species, Populus angustifolia James (narrowleaf cottonwood), in a long‐term, common garden experiment using a bipartite "genotype–species" network perspective. We combine this empirical work with a simulation experiment designed to further investigate how variation among individual tree genotypes can impact network structure. Three findings emerged: (1) the empirical "genotype–species network" exhibited significant network structure with modularity being greater than the highly conservative null model; (2) as would be expected given a modular network structure, the empirical network displayed significant positive arthropod co‐occurrence patterns; and (3) furthermore, the simulations of "genotype–species" networks displayed variation in network structure, with modularity in particular clearly increasing, as genotypic variation increased. These results support the conclusion that genetic variation in a single species contributes to the structure of ecological interaction networks, which could influence ecological dynamics (e.g., assembly and stability) and evolution in a community context.